Demand for Indonesian cocoa beans in a dilemma: Case study Malaysian market - Awan Setya Dewanta (Universitas Islam Indonesia, 2019)
Indonesian cocoa industry has been transforming into a processed cocoa exporter by imposing export taxes. The policy has managed to increase exports of processed cocoa and decreased cocoa bean exports. However, overall export value of cocoa commodities (cacao bean and processed cocoa) has a declining trend, where an increase in the export value of processed cocoa has not been able to offset the decline in the export value of cocoa beans. This study evaluates the impact of the cocoa bean export-tax policy on demand for Indonesian cocoa in the Malaysian market using elasticity and ARDL model. Findings/Originality: This study finds that the demand for Indonesian cocoa is short-term in nature, and the volume of Malaysian demand for Indonesian cocoa is rapidly decreasing because cocoa beans is a complement for other cocoa suppliers. These conditions indicate that the quality of Indonesian cocoa does not meet the standard. That is also indicated by the increase in imports of cocoa beans to meet the processing needs of cocoa in Indonesia